Uterine Clear Cell Carcinoma: Does Adjuvant Chemotherapy Improve Outcomes?. Issue 1 (1st January 2016) - Nguyen, Julie M.V.; Bouchard-Fortier, Geneviève; Bernardini, Marcus Q.; Atenafu, Eshetu G.; Han, Guangming; Vicus, Danielle; Ferguson, Sarah E.; Gien, Lilian T.
Abstract : Objectives: Women with uterine clear cell carcinoma (UCCC) are at high risk of relapse. Adjuvant chemotherapy (CT) is often recommended, although its effectiveness remains controversial. Our objective was to evaluate treatment-related outcomes of patients with UCCC, particularly those treated with adjuvant CT. Methods: In this retrospective cohort study, patients diagnosed with UCCC at 2 academic cancer centers from 2000 to 2014 were included. Clinical, surgical, and pathological data were collected. Survival estimates were obtained using the Kaplan-Meier method and compared by log rank test. Multivariable analysis was used to determine the effect of CT and radiation therapy (RT) on overall survival (OS) and progression-free survival (PFS). Results: We included 146 patients with UCCC, with a median follow-up of 27 months (range, 1–160). Ninety-five (65%) patients presented with stage I to II disease and 51 (35%) with stage III to IV disease. Forty-six percent of patients with clinical stage I were upstaged after surgery: 29% were upstaged to stages III and IV. Thirty-one percent of patients with early-stage disease and 70% with advanced-stage received CT. Among recurrences, the majority had distant relapse in both early-stage (61.5%) and advanced-stage (96.3%) diseases. In both patients with early-stage and advanced-stage diseases, adjuvant CT did not improve OS or PFS. On multivariate analysis, CT was not a significant factor associated with improved PFS (hazard ratio [HR], 1.37; 95% confidence interval [CI], 0.69–2.71; P = 0.37) or OS (HR, 0.58; 95% CI, 0.24–1.38; P = 0.22), whereas RT was associated with improved PFS (HR, 0.51; 95% CI, 0.29–0.90; P = 0.02) and OS (HR, 0.19; 95% CI, 0.09–0.42; P < 0.001). Conclusions: The high rate of upstaging after surgery highlights the importance of lymph node assessment. The high rate of distant recurrence questions the effectiveness of current CT regimens and warrants the development of novel systemic approaches. The role of adjuvant RT deserves further study.